In-situ infiltration performance of different permeable pavements in a employee used parking lot – A four-year study. (1st February 2016) - Kumar, Kuldip; Kozak, Joseph; Hundal, Lakhwinder; Cox, Albert; Zhang, Heng; Granato, Thomas
Abstract: Permeable pavements are being adopted as a green solution in many parts of the world to manage urban stormwater quantity and quality. This paper reports on the measured in-situ infiltration performance over a four-year period since construction and use of three permeable parking sections (permeable pavers, permeable concrete and permeable asphalt) of an employee car parking lot. There was only a marginal decline in infiltration rates of all three pavements after one year of use. However, between years two to four, the infiltration rates declined significantly due to clogging of pores either by dry deposition of particles and/or shear stress of vehicles driving and degrading the permeable surfaces; during the last two years, a greater decline was also observed in driving areas of the parking lots compared to parking slots, where minimal wear and tear are expected. Maintenance strategies were employed to reclaim some of the lost infiltration rate of the permeable pavements to limited success. Despite this decline, the infiltration rates were still four to five times higher than average rainstorm intensity in the region. Thus, these permeable pavement parking lots may have significant ecological importance due to their ability to infiltrate rainwater quickly, reduce the runoff in the catchment area, and also dampen runoff peak flows that could otherwise enter the collection system for treatment in a combined sewer area. Highlights: Permeable pavements were effective in infiltrating rainwater quickly. Infiltration rates of the permeable pavements declined with time due to clogging. Higher traffic caused greater declines in infiltration rate of permeable pavements. Infiltration rate even after four year of use was higher than average rain intensity.